'We just did it as a team': Learning and working on a paediatric interprofessional training ward improves interprofessional competencies in the short- and in the long-term. (4th March 2023) - Bode, Sebastian F. N.; Friedrich, Sebastian; Straub, Christine
Abstract: Purpose: Interprofessional (IP) education is essential for healthcare professionals to prepare them for future IP collaboration. IP training wards (ITWs) have been established for work-based IP education. Short-term effects of ITW placements have been published but long-term results are scarce. There are no reports on ITWs in paediatrics. We established the Interprofessional Training Ward in Paediatrics (IPAPAED) for paediatric nursing trainees and medical students. The aim of the study is to evaluate both short- and long-term outcomes regarding IP competencies of IPAPAED participants. Methods: The study was designed as a prospective, non-randomized trial, using a mixed-methods design. The Interprofessional Socialization and Valuing Scale (ISVS-9A/B) and the Interprofessional Collaboration Scale (ICS) were used for quantitative evaluation, qualitative data were gathered from structured group discussions and free-text comments. Data were collected from 68 IPAPAED participants, before and after the rotation, and 6–34 months later. Results: IPAPAED participants showed increased global scores in the ISVS 9 A/B and rated their communication competencies and their accommodation in IP teams better (ICS). Improvements in communication competency and accommodation persisted at 6–34 months. Conclusions: IP learning and working on IPAPAED had positive short-term effects on interprofessional competencies. Some of these effects persisted on a long-term.